Time Out of Work and Skill Depreciation - Per-Anders Edin; Magnus Gustavsson (Uppsala University, Department of Economics, 2004)
This paper investigates the role of skill depreciation in the relationship between work interruptions and subsequent wages. Using a unique longitudinal dataset, the Swedish part of the International Adult Literacy Survey, we are able to analyze changes in literacy skills for individuals as a function of time out of work. In general, we find statistically strong evidence on a negative relationship between work interruptions and skills. Our analysis suggests that depreciation of general (literacy) skills is economically significant. Our estimates imply that a full year of non-employment is associated with skill losses that are equivalent to moving 5 percentiles down the skill distribution.
Keywords: J13; J24; J31; J69; 330; Work interruptions; Skill depreciation; Unemployment; Wage differentials; Arbeitslosigkeit; Dauer; Qualifikation